THE EFFECT OF FINANCIAL POLICY ON THE PERFORMANCE OF INDUSTRIAL COMPANIES IN THE INSURANCE SUB-SECTOR IN INDONESIA - Saifi, Muhammad (Jurnal Aplikasi Manajemen, 2021)
Companies with good profitability will have better abilities to fund their dividends and investments. Companies experiencing a lack of funding to fund dividend payments and fund investments can use external funding through leverage. The object of this study is the industrial company of the insurance sub-sector; the selection of this object is based on the idea that insurance as a financial product is supposed to give an assurance to its customers regarding the promised coverage. This study is purposed to examine and explain the effect of financial policy on the company and its performance. The analytical method used is Partial Least Square with purposive sampling technique. The sample used is insurance companies listed on the IDX during the 2017-2019 period. Variables used in this study regarding the effect of financial policies on a company's performance are investment opportunity set, dividend policy, capital structure, and firm value. Based on the analysis results, it is shown that the mediation of Capital Structure and Dividend Policy give a significant positive effect on a company's performance as reflected in the firm value obtained. Thus good financial policies can be used as a strategy to attract investors' interest. The results of this study are expected to benefit the company's leadership in optimizing the company's value through the established financial policies.